Calculation of sleep initiation, continuity and architecture indexes. - Jiménez Cruz, J.; Valencia, M. (Revista Mexicana de Ingenieria Biomedica, 1991)
The development of a turbo pascal program is described, which calculates the start and continuity of sleep indexes. The program also generates numbers that are used in the Havard Graphics graphing package to draw the corresponding hypnogram.